Paradigm of Business Ethics in Marketing Practices of Islamic Banking and Financial Institutions - HUSSAIN MOHI-UD-DIN QADRI (International Journal of Islamic Economics and Governance, 2020)
Over the last several decades, Islamic banking and finance (IBF) has experienced a global record growth in finance industry. Its research is evolved from “foundation to strategic implementation paradigm for practitioners”. It addresses the ethnicity of the IBF and marketing of the financial service firms who are interested in marketing IBF services to their customers and provide guidelines to the policy makers, regulators and other stakeholders in market ends. The aim of this paper is to explore the shariah’s role in marketing practices of IBF products, the challenges in the way of practicing Islamic marketing principles along with the proposed underlying paradigm shift towards Muslims customers satisfaction because of the IBF model of 21st century to meet the need of the customers.